Climate variability and deep water mass characteristics in the Aegean Sea - Georgiou, S.; Mantziafou, A.; Sofianos, S.; Gertman, I.; Özsoy, E.; Somot, S.; Vervatis, V. (Atmospheric Processes in the Mediterranean, 2015)
The main objective of this study is to investigate the variability of the thermohaline characteristics of the deep-water masses in the Aegean Sea and the possible impact of the regional atmospheric forcing variability by analyzing the available oceanographic and atmospheric datasets for the period of 1960–2012. During this period the variability of the deep water characteristics of the Aegean sub-basins is found to be very large as well as the diversity of the deep water characteristics among the sub-basins. The Central Aegean seems to play the key role in the Aegean deep water formation processes. Due to its small size, the Aegean Sea surface responds rapidly to the meteorological changes and/or the variability of the lateral fluxes and this variability propagates in the thermohaline characteristics of the deep water masses of the basin through deep water formation processes. There are many episodes characterized by a tight coupling of the atmosphere and the ocean during the examined period, with the Eastern Mediterranean Transient (EMT) being the most prominent case. We suggest that deep water formation is triggered mostly by the combination of preconditioning during early winter and/or previous winters together with the number of subsequent extreme events during present winter and not only by the total amount of the extreme heat loss winter days.
Keywords: Aegean Sea; Climate variability; Deep water